Social marketing campaign for people who inject drugs - Lazový, Peter; Jirešová, Katarína (Adiktologie, 2008)
Injecting drug use is a dangerous way of using drugs, not only related to high risk of HIV/hepatitis transmission, but also to vein damages. Therefore Odyseus created and realized unique educational campaign named PIKADU. The campaign is based on princi- ples of social marketing, aiming to influence everyone attending the needle/syringe exchange program, even drug users who do not want to talk with outreach workers. Campaign was realized in largest Slovak cities and was extended to open-air summer festivals in addition, but it has impact also outside of the cities. The educational campaign had nine „main messages“ (concerning reduction of risks related to injecting drug use), which were widely distributed for 9 months. Every month had one main message. The message was distributed through different carriers: cards (which could be collected to win T-shirt at the end of the campaign), posters, sheets (to secure clean surface during drug preparation), matches, consultations and magazine. The main messages were written in rhymes to ease remembering. During nine months of PIKADU campaign it was accomplished to directly reach 1439 injecting drug users through 5545 contacts with them. One of the points of the campaign was to encourage the participants to spread the main messages inside the community. We assume that by means of secondary spreading of information, the campaign could reach two or three times more people using drugs. The campaign was very successful and resulted to improvement of outreach workers‘ and drug users‘ knowledge (proved by survey). Peter Lazovy is coordinator of needle/ syringe exchange program and vicechairman of Civic association Odyseus, Slovakia. He has master degree of Social work in Commenius University and has finished Drug counselling course, organized by Civic association SANANIM. In Odyseus he works for 4 years, with active participation in outreach work with peple using drugs and sexworkers. In past he worked as a Social counsellor (social work with people in material and social distress).